Effects of a diuretic adjustment algorithm protocol on heart failure admissions: A randomized clinical trial. (June 2021) - Feijó, Maria KEF; Ruschel, Karen Brasil; Bernardes, Daniela; Ferro, Eduarda B; Rohde, Luis E; Biolo, Andreia; Rabelo da Silva, Eneida Rejane
Introduction: The aim of this study was to evaluate the effectiveness of a diuretic adjustment algorithm (DAA) in maintaining clinical stability and reducing HF readmissions using telemonitoring technologies. Methods: Randomized clinical trial of patients with an indication for furosemide dose adjustment during routine outpatient visits. In the intervention group (IG), the diuretic dose was adjusted according to the DAA and the patients received telephone calls for 30 days. In the control group (CG), the diuretic dose was adjusted by a physician at baseline only. Co-primary outcomes were hospital readmission and/or emergency department visits due to decompensated HF within 90 days, and a 2-point change in the Clinical Congestion Score and/or a deterioration in New York Heart Association functional class within 30 days. Results: A total of 206 patients were included. Most patients were male ( n =119; 58%), with a mean age of 62 (SD 13) years. Four patients (2%) in the IG and 14 (7%) in the CG were hospitalized for HF (odds ratio (OR) 0.31 (0.10–0.91); p =0.04). Multivariate analysis showed a reduction of 67% in readmissions and/or emergency department visits due to decompensated HF in the IG compared with the CG (95% CI 0.13–0.88; p =0.027). Regarding the combined outcome of HF readmission and/or emergency department visits or clinical instability, the IG had 20% fewer events than the CG within 30 days (IG: n =48 (23%), CG: n =70 (34%); OR 0.80 (0.63–0.93); p =0.03). Discussion: Using DAA improved the combined outcome in these outpatients, with favorable and significant results that included a reduction in HF admissions and in clinical instability. (NCT02068937)